FIQH MUAMALAH PERSPECTIVE ON INDODAX CRYPTOCURRENCY PAYMENTS: IMPACT ANALYSIS - Mudrikah, Azizah; SW, Oman Fathurohman (Universitas Islam Negeri Mataram, 2024)
This research aims to explain a more in-depth analysis of the effects of using Indodax cryptocurrency payments from the perspective of fiqh muamalah and how it interacts with the principles of fiqh muamalah. This research is qualitative and uses a library research method. The author collects data, analyses it, and concludes the sources of information obtained. The results show that the impact of using Indodax cryptocurrency payments triggers concerns regarding the elements of gharar (uncertainty) and maisir (gambling) due to the highly fluctuating value and speculative nature that are sometimes involved in trading this digital currency. Because legal authorities do Not regulate cryptocurrency and have No Intrinsic Value, Cryptocurrencies can be affected by market manipulation, such as pump-and-dump schemes, where the price of a cryptocurrency is artificially inflated and then sold in large quantities, causing the price to crash. Such practices are a form of fraud and tadlis because they mislead other investors.